Cutaneous leukocytoclastic vasculitis: the roleof lymphocytes and related immune markers - Gambichler, Thilo; Kulik, Magdalena A.; Skrygan, Marina; Rooms, Isabelle; Höxtermann, Stefan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Apart from neutrophils, other immune cells may play a significant pathogenetic role in cutaneous leukocytoclastic vasculitis (CLV). Aim: To investigate lymphocytes and related immunological factors in patients with CLV requiring systemic glucocorticosteroid treatment. Material and methods: Fourteen patients with severe idiopathic CLV were treated with systemic prednisolone in a tapered dose regimen. Ten healthy individuals served as controls. At baseline and post-treatment, we studied inducer/helper and suppressor/cytotoxic T lymphocytes, B lymphocytes, natural killer cells, CD4+CD25++CD127– cells, CD4+CD25+CD39+ cells and FOXP3, transforming growth factor 1 (TGF-1) and interleukin-10 (IL-10) mRNA levels in the blood using flow cytometry and real time polymerase chain reaction (RT-PCR), respectively. On immunohistochemistry, we studied CD4, CD8, granzyme B, TGF-1, and IL-10. Results: Flow cytometry did not show significant differences. The RT-PCR revealed that TGF-1 mRNA expression was significantly higher after therapy when compared to baseline and controls. On immunohistology, baseline CLV lesions showed significantly more CD4+ lymphocytes than post-treated CLV and controls. CD8+ expression was significantly higher after therapy when compared to baseline and controls. Baseline granzyme B was significantly increased when compared to treated CLV and controls. The IL-10 expression of treated CLV was significantly increased when compared to baseline CLV and; baseline CLV IL-10 expression was significantly increased as compared to controls. Conclusions: Circulating T regulatory cells do not play a significant role in the pathogenesis of CLV. T helper cells and granzyme B seem to be involved in the inflammatory cutaneous process of CLV. A resolution of CLV observed after glucocorticosteroid treatment may be mediated via up-regulation of TGF-1 and IL-10 in different compartments.